Fragmented landscapes: aspects of the process of transformations of the landscape structure in the Upper Cuiabá River Basin (1985 and 2022) - Tarachuk , Marcelo Luiz Perini; Godoy, Jeane Aparecida Rombi de; Paula, Diana Carolina Jesus de; Souza, Natallia Sanches e (Electronic Journal "Fórum Ambiental da Alta Paulista", 2024)
The Upper Cuiabá River Basin (BARC) comprises an important source for the water supply of the Metropolitan Region of the Cuiabá River Valley and has undergone major transformations in the period between 1985 and 2022, especially the conversion of land use and occupation to anthropogenic activities. It strongly represents the occupation model adopted in the westernmost portion of the Brazilian Cerrado and concomitantly a pole through which the occupation of the Amazon Rainforest spread, especially the northern region of the State of Mato Grosso. This article aims to analyze the changes that have occurred in BARC by making a comparative analysis between the map of the MapBiomas series collection 8 from the beginning and the end of the available historical series (1985-2022), through the metric comparison of the diversity of the landscape structure using programs based on Geographic Information Systems (GIS). The specific objectives include the elaboration of thematic maps containing the classes of land use and occupation in a raster image and the evaluation of landscape metrics using the Fragstats© software. For this, the metrics were analyzed using the Fragstats© program on BARC's raster images. Finally, it was concluded that there was a process of conversion of forest and savannah formations that were replaced by agricultural crops and the expansion of urbanized areas, changing the composition of the landscape structure through the process of fragmentation and shredding of natural patches.
Keywords: Landscape analysis; Upper Cuiabá River Bay; Landscape structure